'Are Di would of loved it': reanimating Princess Diana through dolls and AI. Issue 4 (2nd October 2022) - Andrews, Phoenix CS
ABSTRACT: Princess Diana is a secular saint whose fame spans generations and borders and has never dimmed. Fiction, fashion, relatability and a diverse and fervent fandom keep Diana current and relevant over 25 years since her death. In this article, I argue that Diana's death and persisting celebrity give fans the freedom to own and play with her image and persona, and to relate to her in new ways informed by an ironic yet emotionally intense online milieu. I demonstrate that these new ways of relating to Diana prove that her digital life after death is not limited to her appearance and demise, but extends towards her attitude to social issues, rendering Diana fandom a political act. To do so, I combine analysis of Diana, digital fandom, dolls and the creation of AI animations. First, I analyse Diana's portrayal in traditional and social media. Second, using a new creative methodology I call 'social media reaction capture', I create images using AI to test audience responses. Finally, I discuss how emerging technologies and cultures enable dead celebrities to live on while handing control of their image and personae to irreverent new audiences, arguing that ironic fandom and playfulness make Diana's sainthood persist.